2022
DOI: 10.3390/ijms23115915
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rodent Model of Hypertensive Cerebral Small Vessel Disease with White Matter Hyperintensities and Peripheral Oxidative Stress

Abstract: Cerebral small vessel disease (CSVD) is the second most common cause of stroke and a major contributor to dementia. Manifestations of CSVD include cerebral microbleeds, intracerebral hemorrhages (ICH), lacunar infarcts, white matter hyperintensities (WMH) and enlarged perivascular spaces. Chronic hypertensive models have been found to reproduce most key features of the disease. Nevertheless, no animal models have been identified to reflect all different aspects of the human disease. Here, we described a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Human CSVD is known to involve inflammatory signaling cascade [ 27 ]. Our previous results also established elevated immune brain response in SBH/y-DS [ 23 ]. To further broaden our understanding of the immune involvement in our model, RNA from rat cortices was studied by RNA-sequencing analysis.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Human CSVD is known to involve inflammatory signaling cascade [ 27 ]. Our previous results also established elevated immune brain response in SBH/y-DS [ 23 ]. To further broaden our understanding of the immune involvement in our model, RNA from rat cortices was studied by RNA-sequencing analysis.…”
Section: Resultssupporting
confidence: 68%
“…Isoflurane was used for both induction (5%) and maintenance (1.5–2%) of anesthesia. We have previously shown that SBH/y-DS invariably developed hypertension after 1 month that persists as long as the DOCA pellet continues to secrete deoxycorticosterone acetate and NaCl is provided in drinking water [ 23 ]. Sham control animals (“SBH/y sham” group ( n = 11)) were subjected to anesthesia, skin incision and suturing without insertion of the DOCA pellet, and rats were provided tap water with no added salt or potassium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For monogenic SVDs, there are also more reliable models of CADASIL [ 21 ], COL4A1/COL4A2 [ 22 , 23 ], CARASIL [ 24 ], TREX [ 25 ]; and while each might start with a different gene-protein abnormality, the consequences at the glio-vascular unit and for the neuron, are similar – altered basement membranes, inflammation, impaired vascular function and secondary tissue damage. Additional models that explore effects of hypertension and diet in sporadic SVD have been developed [ 26 ].…”
Section: What Have We Learned Since the First Workhop In 2017 [ ...mentioning
confidence: 99%
“…Another group proposed to use of deoxy-corticosteroid acetate (DOCA) treated Sabra hypertension prone (SBH/y) rats as a novel model for cSVD. In these animals, the vascular impact of hypertension leading to WMLs and oxidative stress in these animals [163]. In mice, hypertension can be induced by administration of angiotensin II.…”
Section: Hypertensive Animal Modelsmentioning
confidence: 99%